ANALISIS KONDISI FASILITAS SANITASI PASAR DESA PADA MASA PANDEMIK COVID-19 - Yustini Ardillah; Dwi Nopitrisari (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
Background: Corona Virus Disease (Covid-19) is a virus that has only been spreading since 2020, this virus is a new type of virus (SARS-CoV-2). The spread of this virus is very fast which can cause social and economic problems that occur in almost all over the world, including Indonesia. One of the places that can cause the spread of Corona Virus Disease (Covid-19) is the market. The purpose of this study is to analyze the condition of the Randik market sanitation facilities during the Covid-19 pandemic. Methods : This research is a descriptive qualitative research. The information obtained is through in-depth interviews, observation and document review.This research is a descriptive qualitative research. The information obtained is through in-depth interviews, observation and document review. Results and Discussion : The results of this study indicate that the implementation of a healthy market has not met the requirements but is good enough because it refers to the Kepmenkes RI No. 519 of 2008 concerning a healthy market. From the aspect of clean water that has never been tested, bathroom / toilet facilities that do not have a closed trash can, garbage disposal facilities that do not have proper / separate trash boxes between organic and inorganic waste and there is no separation of wet and dry waste , hand washing facilities are already available using soap, equipped with a sink, but there is no provision for a dryer, drainage does not flow because it is blocked by a lot of garbage in the drain and the drainage is not managed first, PHBS on traders and visitors have not implemented requirements such as not using PPE completely while on the market, not maintaining personal hygiene such as not washing hands before and after activities, not maintaining environmental hygiene, often littering. Conclusion : It can be concluded that the implementation of a healthy market has not met the requirements in the guidelines for the Minister of Health No. 519 of 2008 concerning a healthy market. The suggestions from this research are the existence of clean water testing, provision of separate garbage disposal boxes and provide directions for traders and visitors to sort waste.